An unusual case of gross myoglobinuria in a child following Russell's viper (Daboia russelii) envenomation. (January 2019) - Dissanayake, P.V.; Muthukumarana, T.G.W.; Aslam, W.A.M.; Chaminda, S.A.A.; Munasinghe, T.S.; Kularatne, S.A.M.
Abstract: Overt myoglobinuria associated with myotoxicity is a classic feature of sea snake envenomation. Russell's viper bites usually result in coagulopathy, neurotoxicity and nephrotoxicity but rarely myotoxicity has been reported, especially in the Sri Lankan variety ( Daboia russelii ). All those studies have demonstrated mild degree myotoxicity with microscopic level myoglobinuria. We report what is probably the first case of gross myoglobinuria in a child following a Russell's viper bite with biochemical evidence of significant myotoxicity well beyond the levels that have been previously reported. Highlights: Myoglobinuria is a feature of envenomation by sea snakes, certain elapids and vipers in Africa and Central/South America. Only microscopic myoglobinuria has been reported previously following Russell's viper bites in Sri Lanka. We report what is probably the first case of gross myoglobinuria following a Russell's viper bite in a child.